2021
DOI: 10.22141/2308-2097.55.2.2021.233629
|View full text |Cite
|
Sign up to set email alerts
|

Markers of progression of liver fibrotic changes in patients with chronic toxic drug-induced hepatitis

Abstract: Background. In recent years, as a result of the growing expansion of the pharmaceutical market, there has been a clear trend towards an increase in the incidence of chronic toxic drug-induced hepatitis of drug genesis (TDIH). The appearance of fibrosis is considered the most important histological change that determines the further course of the disease. Therefore, the search for non-invasive or minimally invasive markers for assessing fibrotic changes in the liver remains an urgent issue in clinical practice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The analysis of literature data focused on the search for informative serum markers to diagnose severe liver fibrosis has shown that it was reasonable to use different serum markers in chronic diffuse liver diseases of different etiology. So, the study [20] has shown that the most informative serum markers for the diagnosis of severe liver fibrosis in patients with chronic alcoholic hepatitis were levels of tumor necrosis factor-α >2.1 pg/ml and protein-bound hydroxyproline >260.5 μmol/l. Another study [21] has shown a number of parameters, in particular, HBeAg status, viral load, the degree of necroinflammatory activity expressiveness according to alanine aminotransferase indicators, and the degree of tumor necrosis factor-α increase, that should be considered when assessing a risk of severe liver fibrosis in chronic hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of literature data focused on the search for informative serum markers to diagnose severe liver fibrosis has shown that it was reasonable to use different serum markers in chronic diffuse liver diseases of different etiology. So, the study [20] has shown that the most informative serum markers for the diagnosis of severe liver fibrosis in patients with chronic alcoholic hepatitis were levels of tumor necrosis factor-α >2.1 pg/ml and protein-bound hydroxyproline >260.5 μmol/l. Another study [21] has shown a number of parameters, in particular, HBeAg status, viral load, the degree of necroinflammatory activity expressiveness according to alanine aminotransferase indicators, and the degree of tumor necrosis factor-α increase, that should be considered when assessing a risk of severe liver fibrosis in chronic hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in rats with acute periodontitis, its value increases compared to intact animals; in rats with hypothyroidism, it decreases, and in animals with simultaneous manifestation of acute periodontitis and hypothyroidism, the IRI significantly decreases [ 25 ]. The IRI is reduced in patients with non-alcoholic fatty liver disease and chronic hepatitis C. However, in patients with non-alcoholic fatty liver disease, the content of CD8 lymphocytes does not change [ 26 ]. The authors’ research also revealed a relationship between the absolute number of leukocytes, lymphocytes, phagocytic activity, and the IRI [ 27 ].…”
Section: Introductionmentioning
confidence: 99%